Vessel scheduling model with resource restriction considerations for restricted channel in ports. (March 2023) - Jiang, Xing; Zhong, Ming; Shi, Guoyou; Li, Weifeng; Sui, Yi
Highlights: Restricted channel scheduling model with resource restriction consideration. The model can be changed according to the actual needs of different ports. The change of the number of tugs affects the waiting time. The model and algorithm are superior to first come first service strategy. Provide better auxiliary decision-making for the port. Abstract: Restricted channels differ from ordinary channels because of their external environmental factors; they have many restrictions on vessel scheduling. In particular, for ports with restricted channels and harbor basins, these restrictions affect the safety and efficiency of vessel scheduling, resulting in traffic congestion and causing long delays and waiting times for vessels. Therefore, in this study, we use a mathematical optimization model to optimize vessel scheduling in ports with restricted channel to reduce vessel waiting time, improve vessel transportation efficiency, and ensure transportation safety. We simultaneously considered constraints such as complex navigation rules of restricted channel and scheduling resources to develop the mathematical optimization model. An elite selection genetic algorithm (e-GA) with the vessel service sequence as the code is proposed to solve the optimization model. Finally, using the optimization model, a customized model of the Port of Huanghua was developed based on the actual layout and rules of the port and case studies were conducted. The research results prove the rationality and reliability of the proposed optimization model as well as the effectiveness of e-GA and provide basic theoretical support for expanding this research direction. The results show that compared with the traditional first come first service (FCFS) strategy, the optimization model and e-GA can yield better auxiliary decision making for vessel scheduling in restricted channel and have practical significance.